New therapeutic approach to corrosive burns of the upper gastrointestinal tract. Issue 5 (May 1980) - Di Costanzo, J; Noirclerc, M; Jouglard, J; Escoffier, J M; Cano, N; Martin, J; Gauthier, A
Abstract : The therapeutic approach to the management of corrosive burns of the upper gastrointestinal tract leaves a considerable morbidity and a heavy mortality rate. This work evaluates the effectiveness of a new therapeutic approach given to 94 consecutive patients. The management has been based on three major points: (1) the definition of extent of upper gastrointestinal lesions by immediate fibroendoscopy; (2) immediate protection of the upper gastrointestinal tract by total parenteral nutrition in cases with serious burns (41 cases), normal oral nutrition being allowed for minor burns (35 cases); (3) reparative surgical procedures for any of the sequelae of such burns during the fibrosing phase. The results were as follows: (a) healing, depending upon the degree of burn, occurred between eight to 90 days; (b) the frequency of subsequent local complications was small with total parenteral nutrition started a few hours after ingestion of the corrosive product; (c) after reconstructive surgery no serious complications occurred; (d) the overall morbidity stayed at a very low level (four patients). We conclude that the general prognosis of a severe burn of the upper gastrointestinal tract, without other trauma, is appreciably improved by the very early institution of total parenteral nutrition.